The effects of cylinder deactivation on the thermal behaviour and performance of a three cylinder spark ignition engine - Bech, Alexander; Shayler, Paul J.; McGhee, Michael (SAE International, 2016)
A physics based, lumped thermal capacity model of a 1litre, 3 cylinder, turbocharged, directly injected spark ignition engine has been developed to investigate the effects of cylinder deactivation on the thermal behaviour and fuel economy of small capacity, 3 cylinder engines. When one is deactivated, the output of the two firing cylinders is increased by 50%. The largest temperature differences resulting from this are between exhaust ports and between the upper parts of liners of the deactivated cylinder and the adjacent firing cylinder. These differences increase with load. The deactivated cylinder liner cools to near-coolant temperature. Temperatures in the lower engine structure show little response to deactivation. Temperature response times following deactivation or reactivation events are similar. Motoring work for the deactivated cylinder is a minor loss; the net benefit of deactivation diminishes with increasing load. For the NEDC and FTP-75 cycle, the predicted fuel savings are ∼3½ %; the benefit is lower for more transient or highly loaded cycles.